Choosing Ethics Over Morals: A Possible Determinant to Embracing Artificial Intelligence in Future Urban Mobility - Kassens-Noor, E.; Siegel, Josh; Decaminada, Travis (Frontiers in Sustainable Cities, 2021)
Artificial Intelligence (AI) is becoming integral to human life, and the successful wide-scale uptake of autonomous and automated vehicles (AVs) will depend upon people’s willingness to adopt and accept AI-based technology and its choices. A person’s state of mind towards autonomous vehicles’ artificial intelligence (AVAI), such as familiarity or risk-aversion, has an impact on their willingness to adopt the use of AVs. However, one determinant of whether AVAI should be driven by society’s ethics or the driver’s morals, the “state of mind” variable, has not been studied. We asked 1,473 student, staff, and employee respondents at a university campus whether they prefer an AVAI learn their owners own personal morals (one's own principles) or adopt societal ethics (codes of conduct provided by an external source). Respondents were almost evenly split between whether AVAI should rely on ethics (45.6%) or morals (54.4%). People who favor AVAIs adopting society’s ethics are more willing to adopt, more familiar with, and have more favorable perceptions of AVs. We find that individuals who are younger, male, not white, and who have favorable perceptions of AVs express a statistically significantly greater willingness to adopt. Controlling for these factors, we find that individuals’ familiarity with AVs and their beliefs about whether AVs should rely on ethics or morals are not statistically significantly associated with their willingness to adopt AVs. Regardless, to successfully govern artificial intelligence in cities, policy-makers must thus bridge the deep divide between individuals who choose morals over ethics and vice versa.